Theoretical studies and NMR assay of coumarins and neoflavanones derivatives as potential inhibitors of acetylcholinesterase. (August 2020) - de Souza, Luana G.; Moraes, Paula F.; Leão, Raquel A.C.; Costa, Paulo R.R.; Soares, Rosemberg O.; Pascutti, Pedro G.; Figueroa-Villar, Jose D.; Rennó, Magdalena N.
Graphical abstract: Highlights: Synthesized coumarins and neoflavanones derivatives as potential inhibitors of Acetylcholinesterase. The coumarin (12b) presented a good inhibition of Ee AChE. The coumarin (12b ) showed good results for oral bioavailability and permeability according to the rule of five by Lipinski. MD simulations enhanced our understanding about of the interaction of AChE with coumarins and neoflavanones derivatives. Abstract: Currently Alzheimer's disease (AD) is a devastating neurological disorder that mainly affects the elderly. The treatment of AD has as main objective to increase the levels of ACh in the synaptic cleft by inhibiting the cholinesterase enzymes, which are responsible for the degradation of ACh. Twenty one synthesized coumarins and neoflavanones (4-arylcoumarins) and theoretical studies were used to select the most promising ligands for in vitro experimental studies by Nuclear Magnetic Resonance. The eight compounds selected for the experimental study only 12b (effectiveness 68.54 ± 3.22%) was promising AChE inhibitor. This compound (12b ) presents substituents at positions 4, 5, 6, 7 and 8 in a coumarin nucleus, being the most significant characteristic in comparison to the other studied compounds. These results can be used for the design and synthesis of other possible derivatives with inhibitory potential of AChE.